The Impact of Glycoengineering on the Endoplasmic Reticulum Quality Control System in Yeasts - Piirainen, Mari A.; Frey, Alexander D. (Frontiers in Molecular Biosciences, 2022)
Yeasts are widely used and established production hosts for biopharmaceuticals. Despite of tremendous advances on creating human-type N-glycosylation in yeasts, N-glycosylated biopharmaceuticals manufactured by yeasts are still missing on the market. The N-linked glycans fulfill several purposes. They are essential for the properties of the final protein product for example modulating half-lives or interactions with cellular components. Still, while the protein is being formed in the endoplasmic reticulum, the specific glycan intermediates already play crucial roles in the folding of or disposal of proteins that failed to fold in time. However, many of the glycoengineering approaches are based on modifications of the N-glycan processing steps in the endoplasmic reticulum and create intermediates that deviate from the canonical N-glycan structures required for interactions with the lectins of the ER quality control system. In this review we provide a concise overview on the N-glycan biosynthesis, glycan-dependent protein folding and quality control systems and the wide array glycoengineering approaches. Furthermore, we discuss how the current glycoengineering approaches partially or fully by-pass glycan-dependent protein folding mechanisms or create structures that mimic the glycan epitope required for ER associated protein degradation.